Endocrine Society of India management guidelines for patients with thyroid nodules: A position statement - Unnikrishnan, A. G. (Medknow Publications, 2011)
Thyroid nodules are common. Thyroid cancer is rarer. No guidelines exist for management of thyroid nodules in the Indian context and these recommendations are intended for this purpose. The consensus committee reviewed important articles, including previously published consensus statements. Management points were scored according to the level of evidence. These guidelines cover the clinical evaluation and include the interpretation of imaging and fine needle aspiration cytology of thyroid nodules. The guidelines also cover the management of special situations like thyroid incidentalomas, cystic thyroid lesion and nodules detected during pregnancy. The consensus guidelines represent a summary of current medical evidence for thyroid nodule management and the committee has attempted to optimize the guidelines for the clinical practice setting in India.